Red-backed Shrikes (Lanius collurio) adjust the mobbing intensity, but not mobbing frequency, by assessing the potential threat to themselves from different predators - Němec, Michal (Jihočeská univerzita, 2013)
We tested ability to adjust nest defence in the red-backed shrike. We presented dummies of three species of adult bird predators (sparrowhawk, kestrel, and long-eared owl; differing in the potential danger for the defending birds), plus two species of nest predators (jay and magpie; differing in the proportion of nestlings of small passerines in their diets). A dummy pigeon was used as the control. Shrikes regularly attacked all of the dummies tested, with the exception of the magpie and pigeon.
Red-backed Shrikes (Lanius collurio) adjust the mobbing intensity, but not mobbing frequency, by assessing the potential threat to themselves from different predators
Keywords: mobbing; red-backed shrike; nest defence; antipredator behaviour; mobbing; red-backed shrike; nest defence; antipredator behaviour